Perbedaan efektifitas penutupan tubulus dentin antara pasta gigi yang mengandung bioaktif glass (novamin) dan strontium chloride - Profilia Shinta; Ketut Suardita; Moch. Mudjiono (Universitas Airlangga, 2018)
Background : Dentinal hypersensitivity (DH) is a painful clinical condition and is characterized by pain arising from exposed dentin in response to various stimuli. Various treatment modalities are available to treat dentinal hypersensitivity which include at-home and in-office treatment. At home treatment generally consists of a variety of dentrifices containing different constituents like strontium chloride and bioactive glass (Novamin). These agents cause occlusion of dentinal tubules thereby reducing hypersensitivity.Purpose: This study was to evaluate the effects of different desensitizing dentifrices on dentinal tubule occlusion by scanning electron microscopy (SEM) of strontium chloride and bioactive glass (Novamin) pastes in the treatment of dentinehypersensitivity (DH) Methods: sixteen extractedspecimens from bovine incisors teeth with randomized into 2 groups (n=8). The crowns were removed from the root and the crown were sectioned longitudinally into two parts (in a mesiodistaldirection). The cervical toothwere resulting in two samples per tooth.Dentinal tubules were exposedand thesamples provided a 4 mm x 4 mm area of exposed dentinal tubules.Group 1 (treated with strontium chloride), Group 2 (treated with bioactive glass (novamin))After each treatment for seven days, tubule occlusion on dentin were analyzed by scanning electron microscopy (SEM).The data were analyzed using “mann-whitneytest” (p<0.05).Result: Groups bioactive glass (novamin) showed tubule occlusion highest when compared with groups strontium chloride.Conclusion: bioactive glass (novamin) paste showed tubule occlusion highest with strontium chloride